The determinants of insurance companies profitability: empirical evidence of developed and developing countries / Nur Rashikah A.B. Yassin - A.B. Yassin, Nur Rashikah (2018)
Insurance plays a significant role in supporting and maintaining a healthy financial system. Thus, it is important to ensure the insurance companies to operate in profits. Based on S-curve theory, developed and developing countries will react differently to insurance sector due to the macroeconomic factors. The purpose of this study is to find out whether the insurance companies in both developed and developing countries are affecting by the same internal factors or not. The study has taken under 20 insurance companies for developed countries and 20 insurance companies for developing countries for the period of 2011-2016. Multiple regression tools were used in order to achieve the objectives of this study. The study examines the effect of liquidity, company size, growth rate and volume of capital as independent variables on insurance companies’ profitability by using ROA as a proxy. At the end of this study, the study found out that volume of capital is significant for both developed and developing countries. Meanwhile, growth rate seems to only significant to the developed countries.